2011
DOI: 10.1142/s0192415x1100955x
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant, Anti-inflammatory and Antiproliferative Activities of Kalanchoe gracilis (L.) DC Stem

Abstract: Oxidative stress and inflammation are related to several chronic diseases including cancer and atherosclerosis. Kalanchoe gracilis (L.) DC is a special folk medicinal plant in Taiwan. The aim of this study was to evaluate the antioxidant, anti-inflammatory and antiproliferative activities of the methanolic extract and fractions of the stem of K. gracilis. TEAC, total phenolic compound content, total flavonoid content, DPPH radical scavenging activity, reducing power, inhibition of NO production in LPS-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(34 citation statements)
references
References 16 publications
1
32
0
1
Order By: Relevance
“…Furthermore, RVSA40 inhibited the activity of the transcription factor STAT3, constitutively expressed in HEK293 cells, promoting its dephosphorylation by a protein tyrosine phosphatase mediated effect [37]. Studies conducted in macrophages derived from THP-1 monocytes, demonstrated similar effects to these previously described [34,35,36]. Extracts of chamomile, meadowsweet, willow bark and isolated polyphenols present in these extracts as quercetin, apigenin and salicylic acid, were able to suppress the secretion of TNF-α and IL-6 without IL-1β modulation in THP-1 monocytes differentiated with phorbol -12-myristate-13-acetate (PMA) [38].…”
Section: Immune Function and Polyphenolsmentioning
confidence: 78%
See 1 more Smart Citation
“…Furthermore, RVSA40 inhibited the activity of the transcription factor STAT3, constitutively expressed in HEK293 cells, promoting its dephosphorylation by a protein tyrosine phosphatase mediated effect [37]. Studies conducted in macrophages derived from THP-1 monocytes, demonstrated similar effects to these previously described [34,35,36]. Extracts of chamomile, meadowsweet, willow bark and isolated polyphenols present in these extracts as quercetin, apigenin and salicylic acid, were able to suppress the secretion of TNF-α and IL-6 without IL-1β modulation in THP-1 monocytes differentiated with phorbol -12-myristate-13-acetate (PMA) [38].…”
Section: Immune Function and Polyphenolsmentioning
confidence: 78%
“…In murine RAW 264.7 macrophages stimulated by lipopolysaccharide (LPS), a dose dependent decrease on iNOS, IL-1-β and IL-6 mRNA expression and the subsequently nitric oxide (NO), IL-1-β and IL-6 production was observed, when the cells were pre-treated during 1 h with Chinese propolis [32]. Other studies also showed inhibitory effects on iNOS, COX-2 and the inflammatory cytokines TNF-α, IL-1-β e IL-6 after treatment with an crude extract of Lonicera japónica Thunb ( Caprifoliaceae ) [33] or Kalanchoe gracilis [34]. The same inhibitory effect on cytokines was induced with 7- O -methylnaringenina, associating to these changes a decreased phosphorylation of extracellular signal-regulated protein kinases 1 and 2 (ERK1/2) and c-Jun N -terminal kinases (JNK), both important factors involved on the lipopolysaccharide (LPS) activation of cytokines [35].…”
Section: Immune Function and Polyphenolsmentioning
confidence: 99%
“…Da - Huan - Hun , is a Chinese folk medicine in Taiwan, commonly used to alleviate pain, fever, inflammation, and injuries [8–10]. Its bioactive compounds include coumarin, bufadienolides, flavonoids (quercetin, kaempferol, teolin, quercitrin, and eupafolin), and glycosidic derivatives of eupafolin demonstrating antioxidant, anti-inflammatory, and/or antiproliferative activities [1113].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, antioxidant effects of aqueous preparation derived from leaves of K. pinnata have been recently confirmed in animal study on diabetes-induced oxidative stress (Menon et al 2016). Moreover, some information on beneficial effects of extracts isolated from other parts of different Kalanchoe species also appeared, for exmaple Lai et al (2011) demonstrated antioxidant activities of extracts of K. gracilis stem. These authors evaluated antioxidant actions of crude extract and its n-hexane, chloroform, ethyl acetate, n-butanol and aqueous fractions.…”
Section: Discussionmentioning
confidence: 99%